Understanding loneliness: a systematic review of the impact of social prescribing initiatives on loneliness. (July 2021) - Reinhardt, GY; Vidovic, D; Hammerton, C
Aims: The aim of this systematic literature review is to assess the impact of social prescribing (SP) programmes on loneliness among participants and the population. Methods: We followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to search EBSCOHost (CINAHL Complete, eBook Collection, E-Journals, MEDLINE with Full Text, Open Dissertations, PsycARTICLES, and PsycINFO), UK National Institute for Health and Care Excellence (NICE), Web of Science Core Collection, and grey literature. We included studies measuring the effectiveness and impact of SP programmes in terms of loneliness. We excluded systematic reviews and studies without evaluations. Due to the absence of confidence intervals and the low number of studies, we conduct no meta-analysis. Results: From 4415 unique citations, nine articles met the inclusion criteria. The studies do not use uniform measures or randomised samples. All nine studies report positive individual impacts; three report reductions in general practitioner (GP), A&E, social worker, or inpatient/outpatient services; and one shows that belonging to a group reduces loneliness and healthcare usage. Conclusion: The findings of this systematic review indicate that individuals and service providers view SP as a helpful tool to address loneliness. However, evidence variability and the small number of studies make it difficult to draw a conclusion on the extent of the impact and the pathways to achieving positive change. More research is needed into the impact of SP programmes on participants, populations, and communities in terms of loneliness, isolation, and connectedness, especially in light of the surge in SP activity as a key part of pandemic response.